Blocking domain 6 of high molecular weight kininogen to understand intrinsic clotting mechanisms - Pradeep K. Singh; Zu‐Lin Chen; Katharina Horn; Erin H. Norris (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background The contact system is initiated by factor (F) XII activation and the assembly of high molecular weight kininogen (HK) with either FXI or prekallikrein (PK) on a negatively charged surface. Overactivation of this system contributes to thrombosis and inflammation in numerous diseases. To develop effective therapeutics for contact system disorders, a detailed understanding of this pathway is needed. Methods We performed coagulation assays in normal human plasma and various factor‐deficient plasmas. To evaluate how HK‐mediated PK and FXI activation contributes to coagulation, we used an anti‐HK antibody to block access to domain 6 of HK, the region required for efficient activation of PK and FXI. Results FXI's binding to HK and its subsequent activation by activated FXII contributes to coagulation. We found that the 3E8 anti‐HK antibody can inhibit the binding of FXI or PK to HK, delaying clot formation in human plasma. Our data show that in the absence of FXI, however, PK can substitute for FXI in this process. Addition of activated FXI (FXIa) or activated PK (PKa) abolished the inhibitory effect of 3E8. Moreover, the requirement of HK in intrinsic coagulation can be largely bypassed by adding FXIa. Like FXIa, exogenous PKa shortened the clotting time in HK‐deficient plasma, which was not due to feedback activation of FXII. Conclusions This study improves our understanding of HK‐mediated coagulation and provides an explanation for the absence of bleeding in HK‐deficient individuals. 3E8 specifically prevented HK‐mediated FXI activation; therefore, it could be used to prevent contact activation‐mediated thrombosis without altering hemostasis.